A Fuzzy Delphi analytic job demands-resources model to rank factors influencing open innovation. Issue 2 (3rd April 2022) - Alnoor, Alhamzah; Abdullah, Hasan Oudah; AL-Abrrow, Hadi; Wah Khaw, Khai; Al-Awidi, Intisar Abas; Abbas, Sammar; Omrane, Amina
Abstract: This study aims to determine the impact of the job demands-resources model and professional identity on open innovation in the industrial sector by adopting technology as a mediating variable. The factors that influence open innovation were identified based on the Fuzzy Delphi method. Hence, the quantitative (questionnaire survey) design was used to gather 260 employees in the industrial sector. The structural equation model (PLS-SEM) was used to analyse the data. The findings of this study reveal the positive impact of professional identity and feedback on open innovation and the negative impact of time pressure, workload, and work-family imbalance on open innovation. The results highlight vital internal and external factors in creating an organisational climate that encourages open innovation.